Level of Family Knowledge and Elderly Activity in The Elderly Integrated Health Center - Umi Masruro; Zulfikar Muhammad; Tri Nurhudi Sasono (Department of Nursing, Faculty of Health Sciencce, Universitas Brawijaya, 2022)
The elderly Integrated Health Center is one of the government's efforts to foster the elderly health of the elderly. However, problems are often encountered in its implementation, such as the lack of active elderly in the Integrated Integrated Health Center due to the lack of family knowledge about the Elderly Integrated Health Center. We aimed to determine the relationship between the level of family knowledge about the Integrated Health Center of the elderly with the activeness of the elderly in the Integrated Health Center. The design of this study used the Correlation Analytic Description method with the Cross-Sectional approach. The sample had 44 respondents using the Purposive Sampling technique. The questionnaire was used for collecting data, and for processing data, we used the Spearman Rho analysis test. The results showed that there was a relationship between family knowledge level about the Elderly Integrated Health Center and the activeness with the results of the p-value <0.001. Based on this, the level of family knowledge about the Integrated Health Center for the elderly is related to the activeness of the elderly in the Integrated Health Center for the elderly. Thus it is necessary to increase family knowledge about the Integrated Health Center for the elderly so that the elderly can actively participate in the Integrated Health Center for the elderly.